A Comparative Analysis of Foreign Trade of BRICS Countries - Singh, Kalpana (Prabandhan: Indian Journal of Management, 2016)
In 2001, Mr. Jim O'Neill of Goldman Sachs viewed Brazil, Russia, India, and China as the countries from whom much of the world's economic growth was expected to come. To convey this fact, he coined the term BRIC. These emerging economies were forecasted to realize fast economic growth and be larger than some of the developed economies. In 2006, this group officially became a diplomatic-political entity called BRIC. By 2020, the BRIC grouping is projected to account for a third of the global economy (in PPP terms) and contribute about 49% of global GDP growth. By 2050, Brazil, Russia, India, and China will displace most of the current G-7 countries. In 2010, after the inclusion of South Africa, the club of BRICs became the BRICS. The strength of the BRICS economies is of ever increasing importance to the global economy. BRICS's collective contribution to world GDP increased from 11% in 1990 to 25% in 2011. Taken together, the BRICS's contribution to global growth was expected to be around 33% in 2015. Due to so much significance of BRICS's countries in the global economy and international economic relations, the present paper attempted to (a) analyze the major trends in volume and composition of foreign trade of BRICS's countries in the recent past, (b) analyze the major trends in intra-BRICS and extra BRICS foreign trade of BRICS countries in the recent past. The results of the analysis done in the present paper clearly pointed out towards China's dominance in intra BRICS trade. Both, China's share in total BRICS imports and exports are substantially high. However, strengthening cooperation within the bloc will help each country to make better use of those potential comparative advantages.